الأثر الجزائي للجائحة في عقد المساقاة)دراسة فقهية مقارنة (Journal of Humanitarian and Applied Sciences, 2023)
It has evolved in methods of transactions between humans, and what about them? Or the death of a contractor, then, at any time, or at any time, or at any time, or at any time, or the equivalent. And the dispute between it, and accordingly, the provisions of Islamic legislation and the extent of its keenness to provide the principle of consent, justice and equality in contracts between the contractors must be clarified, so the principle of pandemics was required here as one of the means through which the obligation agreed upon between the contractors to remove the damage arising through the new and non-new conditions must be fulfilled. Expected.